Low dielectric loss nonwoven fabric, its production and use

JP7644072B2Active Publication Date: 2025-03-11GUANGDONG SHENGYI SCI TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2022191883
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-12-24
Filing Date
2022-11-30
Publication Date
2025-03-11
Estimated Expiration
2042-11-30

AI Technical Summary

Benefits of technology

【0032】 従来技術に対して、本発明は、以下の有益な効果を有する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007644072000001
    Figure 0007644072000001
  • Figure 0007644072000002
    Figure 0007644072000002
  • Figure 0007644072000003
    Figure 0007644072000003
Patent Text Reader

Abstract

To provide a low dielectric loss non-woven fabric composed of inorganic fibers and a binder, preparation thereof and use thereof.SOLUTION: The binder is one type or a combination of at least two types of fluorine-containing resin emulsion, polyolefin emulsion, polyphenylene ether resin, or cyanate resin. The non-woven fabric according to the present invention has a good dielectric performance and a significant reinforcing effect and can satisfy requirements for various performances of copper clad laminate materials in a high frequency communication field.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention belongs to the technical field of laminates and relates to a low dielectric loss nonwoven fabric, its preparation and its use. [Background technology]

[0002] Copper-clad boards are widely applied in the fields of mobile phones, personal computers, vending machines, communication base stations, satellites, wearable devices, pilotless automobiles, drones and smart robots, and are one of the important basic materials in the electronic communication and information industry. Fluorine-containing resins, represented by polytetrafluoroethylene (PTFE), are ideal copper-clad board substrates because they have multiple excellent performances such as low dielectric constant, low dielectric loss, high thermal stability and chemical stability that other polymer resins cannot achieve. Since fluorine-containing resins have high flexibility of polymer chains, it is usually necessary to introduce inorganic materials to improve the mechanical strength of fluorine-containing resin-based copper-clad boards. For example, CN101857708A discloses that glass fiber cloth is immersed in a fluorine resin mixture and baked to obtain PTFE linoleum, but because the glass cloth is weaved in the warp and weft directions, the produced PTFE copper-clad board is not uniform, and the dielectric constant, CTE and dielectric loss at different points of the copper-clad board are different, resulting in different signal transmission delays at different points.

[0003] As the demand for isotropy in high frequency copper clad boards becomes stronger, there is a need to develop an isotropic reinforcing material that allows PTFE composites to have excellent Dk matching, extremely low dielectric loss, and mechanical strength superior to that of PTFE films without reinforcing materials. Currently, there are no isotropic reinforcing materials with extremely low dielectric loss.

[0004] Although conventional nonwoven fabrics have the characteristics of reinforcement and isotropy, they generally use epoxy-based adhesives, acrylate-based adhesives, melamine-based adhesives, or polyvinyl alcohol-based adhesives, which have large dielectric losses. The dielectric losses of epoxy-based adhesives, acrylate-based adhesives, melamine-based adhesives, or polyvinyl alcohol-based adhesives are large, and are much larger than the dielectric losses of hydrocarbon resins, polyphenylene ether resins, or PTFE resins used in mainstream high-frequency peripheral products. When conventional nonwoven fabrics are used in high-frequency products, they may lose the dielectric advantages of hydrocarbon resins, polyphenylene ether resins, or PTFE resins. Therefore, those skilled in the art have been studying how to overcome the anisotropy caused by the warp and weft knitting of glass fiber cloth by utilizing the characteristics of reinforcement and low dielectric loss of glass fiber cloth, for example, by opening glass cloth and pretreating glass cloth to soak it in resin, thereby reducing defects caused by warp and weft knitting. Summary of the Invention

[0005] In view of the deficiencies in the prior art, the present invention aims to provide a low dielectric loss nonwoven fabric, its preparation and use. The nonwoven fabric of the present invention has good dielectric performance and remarkable reinforcing effect, and can meet various performance requirements of copper-clad plate materials in the field of high frequency communication.

[0006] In order to achieve the object, the present invention provides the following technical solutions.

[0007] In one aspect, the present invention provides a low dielectric loss nonwoven fabric comprising inorganic fibers and an adhesive, wherein the adhesive is any one or a combination of at least two of a fluorine-containing resin emulsion, a polyolefin emulsion, a polyphenylene ether resin, and a cyanate resin.

[0008] In the present invention, by using the adhesive, the nonwoven fabric has low dielectric loss, good uniformity, consistent thickness, consistent anisotropic fiber distribution, and high tensile strength, and a low dielectric loss high frequency copper foil clad board can be produced by adding a large amount of dielectric filler when soaking in low dielectric loss resin.

[0009] In the present invention, the low dielectric loss nonwoven fabric refers to a nonwoven fabric having a dielectric loss of less than 0.0015 (10 GHz).

[0010] Preferably, in the low dielectric loss nonwoven fabric, the weight percentage of inorganic fibers is 60 to 95% (e.g., 60%, 62%, 65%, 68%, 70%, 73%, 75%, 78%, 80%, 83%, 85%, 88%, 90%, 93% or 95%), and the weight percentage of adhesive is 5 to 40% (e.g., 5%, 8%, 10%, 15%, 18%, 20%, 23%, 25%, 28%, 30%, 33%, 35%, 38% or 40%).

[0011] The adhesive is any one or a combination of at least two of a fluorine-containing resin emulsion, a polyolefin emulsion, a polyphenylene ether resin, and a cyanate resin. The adhesive is obtained by adding a solvent to the fluorine-containing resin emulsion, the polyolefin emulsion, the polyphenylene ether resin, or the cyanate resin as necessary, and dissolving and diluting the fluorine-containing resin emulsion, the polyolefin emulsion, the polyphenylene ether resin, or the cyanate resin to an appropriate viscosity.

[0012] In view of its low dielectric performance, the adhesive is preferably a fluorine-containing resin emulsion.

[0013] Preferably, the fluorine-containing resin emulsion is any one or a combination of at least two selected from a polyperfluoroethylene propylene emulsion, a polyvinylidene fluoride emulsion, a tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer emulsion, an ethylene-tetrafluoroethylene copolymer emulsion, a polychlorotrifluoroethylene emulsion, and an ethylene-chlorotrifluoroethylene copolymer emulsion.

[0014] Preferably, the solid content of the fluorine-containing resin emulsion is 30 to 70%, for example, 30%, 35%, 38%, 40%, 45%, 50%, 55%, 60%, 65% or 70%.

[0015] Preferably, in the fluorine-containing resin emulsion, the particle size of the fluorine-containing resin is 0.10 μm to 0.40 μm.

[0016] In this specification, the particle size of the fluororesin emulsion is measured by a laser diffraction method, and the measuring instrument is a Malvern laser particle size distribution analyzer (model number MS3000). In this specification, the dielectric constant and dielectric loss are measured by a split post dielectric resonator (SPDR) method, and the frequency is 10 GHz.

[0017] Preferably, the polyolefin emulsion is any one or a combination of at least two selected from an unsaturated polybutadiene resin emulsion, a styrene-butadiene-styrene triblock copolymer (SBS) emulsion, a hydrogenated styrene-butadiene-styrene triblock copolymer (SEBS) emulsion, and a styrene-butadiene resin emulsion. The solid content of the polyolefin emulsion is 30 to 70%, for example, 30%, 35%, 38%, 40%, 45%, 50%, 55%, 60%, 65%, or 70%.

[0018] Preferably, the inorganic fibers are any one or a combination of at least two selected from E glass fibers, NE glass fibers, L glass fibers, and quartz fibers.

[0019] Preferably, the average diameter of the inorganic fibers is less than 10 microns, such as 9 microns, 8 microns, 7 microns, 6 microns, 5 microns, 4 microns, 3 microns, 2 microns or 1 micron, preferably 1 to 5 microns.

[0020] Preferably, the average length of the inorganic fibers is 1 to 100 mm, for example, 100 mm, 90 mm, 80 mm, 70 mm, 60 mm, 50 mm, 40 mm, 30 mm, 20 mm, 10 mm, or 5 mm. The average diameter and average length of the inorganic filler in the present invention are both observed and measured by a scanning electron microscope.

[0021] Preferably, the unit weight of the low dielectric loss nonwoven fabric is 20 to 200 grams / square meter, for example, 20 grams / square meter, 25 grams / square meter, 30 grams / square meter, 35 grams / square meter, 40 grams / square meter, 50 grams / square meter, 60 grams / square meter, 80 grams / square meter, 100 grams / square meter, 120 grams / square meter, 150 grams / square meter, 180 grams / square meter or 200 grams / square meter, and preferably 20 to 100 grams / square meter.

[0022] In another aspect, the present invention provides a method for producing a low dielectric loss nonwoven fabric, comprising mixing inorganic fibers and an adhesive, soaking the mixture, forming the mixture into a paper, and drying the paper in an oven to obtain the low dielectric loss nonwoven fabric.

[0023] Preferably, the immersion time is 40 to 50 minutes, for example, 40 minutes, 43 minutes, 45 minutes, 48 ​​minutes or 50 minutes.

[0024] Preferably, the oven drying temperature is 120 to 150°C, for example, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C or 150°C.

[0025] If the adhesive is selected from a fluororesin emulsion, an additional sintering step is required after oven drying so that the fluororesin melts and forms a film.

[0026] Preferably, the sintering temperature is 220° C. to 370° C., for example, 220° C., 230° C., 250° C., 270° C., 290° C., 300° C., 320° C., 340° C., 360° C. or 370° C., and the sintering time is 28 to 30 minutes.

[0027] In another aspect, the present invention provides a prepreg comprising the low dielectric loss nonwoven fabric described above and a resin composition deposited thereon by dipping.

[0028] Preferably, the resin composition is a fluorine-containing resin emulsion.

[0029] Preferably, the fluorine-containing resin emulsion is any one or a combination of at least two selected from a polyperfluoroethylene propylene emulsion, a polyvinylidene fluoride emulsion, a tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer emulsion, an ethylene-tetrafluoroethylene copolymer emulsion, a polychlorotrifluoroethylene emulsion, and an ethylene-chlorotrifluoroethylene copolymer emulsion.

[0030] In another aspect, the present invention provides a copper clad board comprising a copper foil and the prepreg described above.

[0031] In another aspect, the present invention provides a printed circuit board comprising a copper foil and a prepreg as described above.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] The nonwoven fabric of the present invention has low dielectric loss, good uniformity, consistent thickness, consistent anisotropic fiber distribution, and high tensile strength. When a low dielectric loss resin is soaked in the nonwoven fabric, a high frequency copper clad board with low dielectric loss and high peel strength can be manufactured by adding a large amount of dielectric filler. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0034] The technical solution of the present invention will be further described below by means of specific embodiments. Those skilled in the art should understand that the above examples are only for understanding the present invention, and should not be regarded as specifically limiting the present invention.

[0035] The raw materials used in the following examples and comparative examples are as follows.

[0036] FEP resin emulsion: particle size 0.20 μm, solid content 50 wt%, manufactured by Daikin Japan Ltd., model number: ND-110.

[0037] PFA resin emulsion: particle size 0.20 μm, solid content 55 wt%, manufactured by Daikin Japan Ltd., model number: AD-2CR.

[0038] PTFE resin emulsion: particle size 0.25 μm, solid content 55 wt%, manufactured by Daikin Japan Ltd., model number: D210C.

[0039] Polyolefin emulsion: particle size 0.1 μm, solid content 45 wt%, sample from Beijing Yanshan Petrochemical.

[0040] Polyphenylene ether adhesive: 100 parts of vinyl modified polyphenylene ether (Mitsubishi Gas OPE-2ST) was weighed out and dissolved in toluene solvent, and the mixture was stirred uniformly to obtain a polyphenylene ether adhesive.

[0041] Low thermal expansion coefficient resin A: 450 g of the above PTFE resin emulsion was weighed out and mixed at high speed for 2 hours to obtain a uniform resin composition.

[0042] Thermosetting resin A: 30 parts by weight of ethylene propylene rubber (number average molecular weight 80,000 g / mol, Lion Chemical Company, USA), 40 parts by weight of polybutadiene (molecular weight 3,200 g / mol, Nippon Soda Co., Ltd.), and 2 parts by weight of benzoyl peroxide (Shanghai Kanglong Bioscience and Technology Co., Ltd.) were dissolved in 50 parts by weight of xylene and mixed uniformly to obtain a uniform resin composition.

[0043] Thermosetting resin B: 70 parts by weight of methacrylate block polyphenylene ether resin MMA-PPE (SA9000, SABIC) and 70 parts by weight of toluene solvent were mixed and completely dissolved to obtain a functional polyphenylene ether resin solution, and then 30 parts by weight of styrene-butadiene copolymer R100 (Sartomer) was added as a crosslinking curing agent, 3 parts by weight of cumene peroxide DCP was added as an initiator, and 15 parts by weight of A bromine flame retardant, ethyl-bis(tetrabromophthalimide) BT-93W (Albemarle Company: bromine content 67.2%), was added, and the mixture was mixed with toluene and dissolved under stirring to obtain a homogeneous resin composition.

[0044] E-glass fiber with an average diameter of 5 μm: China Jushi Co., Ltd.

[0045] NE glass fiber with an average diameter of 5 μm: China Jushi Co., Ltd.

[0046] Quartz fibers with average diameters of 1 μm and 5 μm: China Shenjiu

[0047] E-glass fiber with average diameter of 8μm: China Jushi Co., Ltd.

[0048] Nonwoven fabrics made from epoxy adhesive and E-glass fibers with an average diameter of 13 μm: Shaanxi Huate

[0049] Nonwoven fabrics made from acrylate adhesive and E-glass fibers with an average diameter of 13 μm: Shaanxi Huate

[0050] Nonwoven fabric made from melamine adhesive and E-glass fiber with an average diameter of 13 μm: Shaanxi Huate.

[0051] Example 1

[0052] In this embodiment, a low dielectric loss nonwoven fabric is provided, which is made of glass fiber and an adhesive, and the adhesive is an FEP emulsion.

[0053] A specific manufacturing method includes the following steps.

[0054] 92 parts by weight of E-glass fiber (average diameter 5 microns) and 8 parts by weight of FEP adhesive were soaked for 45 minutes and molded by papermaking. After that, it was dried in an oven at 150°C and then sintered in a high-temperature oven environment at 300°C for 30 minutes. After taking it out and cooling, nonwoven fabric A with a unit weight of 20 grams / m2 was produced.

[0055] Example 2

[0056] 85 parts by weight of NE glass fiber (average diameter 5 microns) and 15 parts by weight of FEP adhesive were soaked for 45 minutes, and molded by papermaking. Then, after drying in an oven at 150°C, it was sintered in a high-temperature oven environment at 300°C for 30 minutes. After taking it out and cooling, nonwoven fabric B with a unit weight of 75 grams / m2 was produced.

[0057] Example 3

[0058] 70 parts by weight of quartz fiber (average diameter 1 μm and 5 μm, weight ratio 1:4) and 30 parts by weight of FEP adhesive were soaked for 45 minutes and molded by papermaking. After that, it was dried in an oven at 140 ° C, and then sintered in a high-temperature oven environment at 220 ° C for 28 minutes. After taking it out and cooling, nonwoven fabric C with a unit weight of 75 grams / square meter was produced.

[0059] Example 4

[0060] 85 parts by weight of E-glass fiber (average diameter 8 microns) and 15 parts by weight of FEP adhesive The mixture was immersed for 45 minutes and molded by papermaking. It was then dried in an oven at 140°C and sintered in a high-temperature oven at 350°C for 28 minutes. After being taken out and cooled, nonwoven fabric D with a unit weight of 75 grams / m2 was produced.

[0061] Example 5

[0062] 85 parts by weight of E glass fiber (average diameter 8 microns) and 15 parts by weight of polyolefin adhesive were soaked for 45 minutes and molded by papermaking. Then, it was dried in an oven at 120°C. After taking it out and cooling, nonwoven fabric E with a unit weight of 120 grams / m2 was produced.

[0063] Example 6

[0064] 85 parts by weight of E-glass fiber (average diameter 8 microns) and 15 parts by weight of vinyl-modified polyphenylene ether (Mitsubishi Gas OPE-2ST) adhesive were immersed for 45 minutes and molded by papermaking. Then, it was dried in an oven at 200°C. After removing and cooling, nonwoven fabric F with a unit weight of 120 grams / m2 was produced.

[0065] The main materials and parameters of the nonwoven fabrics in the above-mentioned examples are summarized in Table 1. [Table 1]

[0066] Example 7

[0067] In this embodiment, a PTFE copper clad plate is provided, the manufacturing method of which specifically includes the following steps:

[0068] Step (1): A gum solution of low thermal expansion coefficient resin A was impregnated into the nonwoven fabric A in Example 1 using a sizing machine to obtain a prepreg H having a sizing resin content of 90%.

[0069] Step (2): The prepreg H obtained in step (1) was placed in a vacuum oven at 100°C and baked for 1 hour to remove moisture, then baked at 260°C for 1 hour to remove the auxiliary agent, and finally baked at 350°C for 10 minutes to obtain an adhesive sheet having a thickness of 0.25 mm.

[0070] Step (3): A 1 oz copper foil was coated and laminated on both the top and bottom sides of one adhesive sheet, and a pressure of 400 PSI was applied (maximum temperature was 380°C, and holding time was 60 minutes) to obtain a PTFE copper-clad plate.

[0071] Example 8

[0072] Prepreg I was obtained in the same manner as in Example 7, except that nonwoven fabric B was used instead of nonwoven fabric A in step (1).

[0073] Example 9

[0074] Prepreg J was obtained in the same manner as in Example 7, except that nonwoven fabric C was used instead of nonwoven fabric A in step (1).

[0075] Example 10

[0076] Prepreg K was obtained in the same manner as in Example 7, except that nonwoven fabric D was used instead of nonwoven fabric A in step (1).

[0077] Example 11

[0078] In this embodiment, a high frequency circuit board is provided, the manufacturing method of which specifically includes the following steps:

[0079] Step (1): A gum solution of thermosetting resin A was impregnated into nonwoven fabric E in Example 5 using a sizing machine to obtain prepreg M having a sizing resin content of 90%.

[0080] Step (2): The prepreg M from step (1) was placed in an oven at 100° C. and baked for 1 hour to remove the solvent, thereby obtaining an adhesive sheet.

[0081] Step (3): A high-frequency circuit board was manufactured by covering and laminating 1 oz copper foil on both the upper and lower sides of the resin layer of one adhesive sheet, and curing the laminate in a press machine. The curing temperature was 200°C, the curing time was 90 minutes, and the curing pressure was 50 kg / cm. 2 It is.

[0082] Example 12

[0083] In this embodiment, a high frequency circuit board is provided, the manufacturing method of which specifically includes the following steps:

[0084] Step (1): A gum solution of thermosetting resin B was impregnated into nonwoven fabric F in Example 6 using a sizing machine to obtain prepreg N having a sizing resin content of 90%.

[0085] Step (2): The prepreg N in step (1) was dried in an oven at 100° C. to remove the toluene solvent, thereby producing a pressure-sensitive adhesive sheet.

[0086] Step (3): Cover both the top and bottom of the resin layer of one adhesive sheet with 1 oz copper foil, and cure the laminate in a vacuum for 90 minutes using a press (curing pressure of 50 kg / cm). 2 and the curing temperature is 200°C), and a high-frequency circuit board was manufactured.

[0087] Comparative Example 1

[0088] The procedure was the same as in Example 7, except that in step (1), nonwoven fabric A was replaced with a nonwoven fabric of epoxy adhesive.

[0089] Comparative Example 2

[0090] The same procedure was carried out as in Example 7, except that in step (1), instead of nonwoven fabric A, an acrylate adhesive was used.

[0091] Comparative Example 3

[0092] The procedure was the same as in Example 7, except that in step (1), nonwoven fabric A was replaced with a nonwoven fabric having a melamine adhesive.

[0093] Comparative Example 4

[0094] The procedure is the same as in Example 11, except that in step (1), non-woven fabric E is replaced with a non-woven fabric with an epoxy adhesive.

[0095] Comparative Example 5

[0096] The procedure was the same as in Example 12, except that in step (1), nonwoven fabric F was replaced with a nonwoven fabric coated with an epoxy adhesive.

[0097] Comparative Example 6

[0098] The same as in Example 7, except that in step (1), the adhesive in nonwoven fabric A is in excess, and the ratio is 50%.

[0099] Performance evaluation was carried out on the copper-clad boards or high-frequency circuit boards in Examples 7 to 12 and Comparative Examples 1 to 6. The method was as follows. 1. Dk and Df: Measured by the split post dielectric resonator (SPDR) method. The measurement condition is A state, and the frequency is 10GHz. 2, Peel strength: GB / T 4722-2017 7.2 method.

[0100] The test results are shown in Tables 2 and 3. [Table 2] [Table 3]

[0101] From Tables 2 and 3, the following can be seen:

[0102] In Examples 7 to 10, by mixing PTFE with a nonwoven fabric made with a low-loss adhesive to produce a copper-clad board, the dielectric loss was lower (Dk(10 GHz) was lower than 2.26, and Df(10 GHz) was 0.0013) and the peel strength was 1.3 N / mm or more, which is clearly superior to the performance of the copper-clad boards produced with general nonwoven fabrics in Comparative Examples 1 to 3.

[0103] In Example 11 and Comparative Example 4, by using a nonwoven fabric made with a low-loss adhesive and a hydrocarbon system to manufacture a copper-clad board, the dielectric loss and peel strength were clearly superior to the performance of the copper-clad board made with a general nonwoven fabric in Comparative Example 4.

[0104] In Example 12 and Comparative Example 5, copper-clad boards were manufactured using a polyphenylene ether system and a nonwoven fabric made with a low-loss adhesive, and the dielectric loss and peel strength were clearly superior to those of the copper-clad board manufactured with a general nonwoven fabric in Comparative Example 5.

[0105] The amount of low-loss adhesive used in Comparative Example 6 was too much, so the dielectric loss of the plate was too high.

[0106] The present invention describes the low dielectric loss nonwoven fabric of the present invention, its preparation and its use through the above examples, but the applicant declares that the present invention is not limited to the above examples, that is, the present invention does not have to be implemented by the above examples. It is clear to those skilled in the art that any improvements to this application, equivalent replacement of each raw material of the product of this application and addition of auxiliary components, selection of specific embodiments, etc. are all within the protection scope and disclosure scope of this application.

Claims

1. A low dielectric loss nonwoven fabric made of inorganic fibers and an adhesive, the adhesive is any one or a combination of at least two of a fluorine-containing resin emulsion, a polyolefin emulsion, a polyphenylene ether resin, or a cyanate resin; the fluorine-containing resin emulsion is any one or a combination of at least two selected from a polyperfluoroethylene propylene emulsion, a polyvinylidene fluoride emulsion, a tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer emulsion, an ethylene-tetrafluoroethylene copolymer emulsion, a polychlorotrifluoroethylene emulsion, and an ethylene-chlorotrifluoroethylene copolymer emulsion, The low dielectric loss nonwoven fabric is characterized in that the weight percent of the inorganic fiber is 60 to 95% and the weight percent of the adhesive is 5 to 40%.

2. 2. The low dielectric loss nonwoven fabric according to claim 1, wherein the adhesive is a fluorine-containing resin emulsion.

3. 2. The low dielectric loss nonwoven fabric according to claim 1, wherein the solids content of the fluororesin emulsion is 30 to 70%.

4. 2. The low dielectric loss nonwoven fabric according to claim 1, wherein the particle size of the fluororesin in the fluororesin emulsion is 0.10 μm to 0.40 μm.

5. The low dielectric loss nonwoven fabric according to claim 1, wherein the polyolefin emulsion is any one or a combination of at least two selected from the group consisting of an unsaturated polybutadiene resin emulsion, a styrene-butadiene-styrene triblock copolymer emulsion, a hydrogenated styrene-butadiene-styrene triblock copolymer emulsion, and a styrene-butadiene resin emulsion.

6. 2. The low dielectric loss nonwoven fabric according to claim 1, wherein the polyolefin emulsion has a solid content of 30 to 70%.

7. 2. The low dielectric loss nonwoven fabric according to claim 1, wherein the inorganic fibers are any one or a combination of at least two of E glass fibers, NE glass fibers, L glass fibers, and quartz fibers.

8. 2. The low dielectric loss nonwoven fabric according to claim 1, wherein the inorganic fibers have an average diameter of less than 10 microns.

9. 2. The low dielectric loss nonwoven fabric according to claim 1, wherein the inorganic fibers have an average length of 1 to 100 mm.

10. 2. The low dielectric loss nonwoven fabric according to claim 1, wherein the unit weight of the low dielectric loss nonwoven fabric is 20 to 200 grams per square meter.

11. A method for producing the low dielectric loss nonwoven fabric according to any one of claims 1 to 10, The manufacturing method includes the steps of mixing inorganic fibers and an adhesive, immersing the inorganic fibers in the adhesive, forming the fibers into a sheet by papermaking, and drying the sheet in an oven to obtain the low dielectric loss nonwoven fabric.

12. A prepreg comprising the low dielectric loss nonwoven fabric according to any one of claims 1 to 10 and a resin composition deposited thereon by dipping.

13. The prepreg according to claim 12, wherein the resin composition is a fluorine-containing resin emulsion.

14. The prepreg according to claim 12, characterized in that the fluorine-containing resin emulsion is any one or a combination of at least two selected from the group consisting of polyperfluoroethylene propylene emulsion, polyvinylidene fluoride emulsion, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer emulsion, ethylene-tetrafluoroethylene copolymer emulsion, polychlorotrifluoroethylene emulsion, and ethylene-chlorotrifluoroethylene copolymer emulsion.

15. A copper-clad board comprising copper foil and the prepreg according to claim 12.

16. A printed circuit board comprising a copper foil and the prepreg of claim 12.

Citation Information

Patent Citations

  • Circuit substrate and preparation method thereof

    CN103755989A

  • Antibacterial glass fiber air filter paper and preparation method thereof

    CN108978350A

  • Glass fiber paper and its production

    JP1993247882A

  • Glass cloth and laminated plate

    JP1998310967A

  • Quartz glass fiber, quartz glass nonwoven fabric, and filter

    JP2004352576A